Designing quantitative telemedicine research. (October 2017) - Wade, Victoria; Barnett, Adrian G; Martin-Khan, Melinda; Russell, Trevor
When designing quantitative trials and evaluation of telehealth interventions, researchers should think ahead to the intended way that the intervention could be implemented in routine care and consider how trial participants with similar characteristics to the target population can be included. The telehealth intervention and the context in which it is placed should be clearly described, and consideration given to conducting pragmatic trials in order to show the effect of telehealth in complex environments with rapidly changing technology. Types of research designs, comparators and outcome measures are discussed and common statistical issues are introduced.